LAJU DEKOMPOSISI SERESAH DAN KETERSEDIAAN UNSUR HARA MAKRO DI BAWAH TEGAKAN JATI (Tectona grandis) DI KABUPATEN KUPANG - Mau, Astin Elise; Seran, Wilhelmina; Pellondou, Mamie E. (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2022)
Teak (Tectona grandis) is one type of plant that has the ability to adapt in dry climates such as in NTT. The availability of nutrients in the soil, especially under teak stands in forest areas is strongly influenced by the amount of organic matter in the form of litter that falls to the forest floor and the rate of decomposition of this type of litter. The research, which was conducted in Amabi Oefeto sub-district, Kupang Regency, which is under the management of KPH Kupang Regency, aims to determine the rate of decomposition and the content of macronutrients under teak stands. The results showed that the rate of decomposition of litter under teak stands on the 30th day of sampling was 0.072 gram/day. As for the content of macro nutrients based on the criteria for assessing the chemical properties of soil (1983), C organic under Teak (Tectona grandis) stands was included in the low criteria, which is worth 1.135%, total N was included in the medium criteria, which was 0.5%, total P was included in the criteria. very high, which is 90.326 mg/100 g of soil, available P is included in the very high criteria, which is worth 35.872 ppm and K-dd is included in the high criteria, which is 0.92 me/100 g of soil.